Papillary glioblastoma exhibiting a neuroradiological cyst with a mural nodule: A case report. Issue 2 (January 2019) - Homma, Taku; Hanashima, Yuya; Maebayashi, Toshiya; Nakanishi, Yoko; Ishige, Toshiyuki; Ohta, Takashi; Yoshino, Atsuo; Hao, Hiroyuki
Abstract: Rationale: Glioblastomas are malignant, infiltrating gliomas classified as grade IV by the World Health Organization. Genetically, most glioblastomas do not exhibit the isocitrate dehydrogenase ( IDH ) 1/2 gene mutation and rarely harbor the 1p/19q co-deletion. Neuroradiologically, glioblastomas rarely form a cyst with a mural nodule lesion. Patient concerns: In this study, a 78-year-old woman, with speech difficulty and forgetfulness, had a cystic tumor with a mural nodule in the right frontoparietal lobe. Therefore, partial tumor resection was performed. Diagnosis: Histopathology of the tumor, a glioblastoma, exhibited pseudopapillary features with non-hyalinized capillary cores and rich mini-gemistocytic cells. Genetic analysis of the tumor revealed co-deletion of 1p36/19q13, with wild-type IDH . Interventions: The patient underwent a combination of postoperative radiotherapy and temozolomide chemotherapy before leaving the hospital. After discharge, she was treated by 20 courses of temozolomide chemotherapy. Outcomes: The patient is free from tumor recurrence 23 months after the operation. Lessons: We present a unique case of glioblastoma that exhibited novel neuroradiological, histopathological, and genetic features with a favorable prognosis for the patient. Therefore, a compilation of similar cases with clinicopathological and genetic analyses to characterize this unique glioblastoma is critical. Clinical evidence will help develop effective therapeutic approaches to improve prognosis in patients with glioblastoma.